The Monolingual Lusoga Dictionary Faced with Demands from a New User Category - Nabirye, Minah; de Schryver, Gilles-Maurice (Lexikos, 2010)
ABSTRACT: In this article, a case is presented of an existing dictionary that is aimed at users with a minimum of primary 7 education, now faced with demands from users in primary 1–3. The reason for this demand is the result of the fact that Lusoga is currently being implemented as a medium of instruction in Uganda, in an environment where there is hardly any literature to serve the intended purpose. A review of the existing literature in and on Lusoga shows that the monolingual Lusoga dictionary — Eiwanika ly’Olusoga (WSG) — is the only reference work with essential information, in Lusoga, that can initiate the teaching of Lusoga at the elementary level. Although the information in the WSG may fit the purpose at hand, that information is mainly presented as a summary, with statements of conclusions only. Explanations to ease its access to the new user are thus missing. Findings from a pilot study conducted by the National Curriculum Development Centre on the implementation of the teaching of Lusoga reveal that the new user is not only the primary 1–3 pupil, but also the teacher who will need to instruct that pupil. Since children’s literature requires additional consideration beyond what can be presently availed, and since the WSG was actually compiled for an advanced user, the focus is shifted from the primary 1–3 pupil to the primary teacher. For that teacher, it is suggested to compile an additional Guide, expanding on the various extra-matter texts and especially the Language Portrait found in the WSG. This is done on the assumption that once the information is expanded and re-represented, a teacher will be able to combine the information in the Guide with that in the WSG, in order to make a Lusoga syllabus from which to draft Lusoga lessons. Although the ideal would of course be to be able to produce fully-fledged customised primers from scratch, this article’s main argument is that in the absence of both human and financial resources to do so, one can reuse and expand on the data found in an existing higher-level dictionary. OBUFUNZE: Eiwanika ly’Olusoga lizuuseeku omukozesa ataali muluubilile. Mu lupapula muno mulagibwamu engeli Eiwanika ly’Olusoga elyawandiikilwa omukozesa atuuseeku mu kyomusanvu bwe lizuuseeku omukozesa okuva mu kibiina kyolubelyebelye okutuuka mu kyokusatu. Kino kiidhie lwa kuba ensomesa y’olulimi Olusoga eli kuteebwa mu nkola aye ng’ebyetaagisa okutuukiliza omulimu guno bikaali kutuukilizibwa. Okwekeenenia kw’ebiwandiiko ebiliwo ku oba mu Lusoga ebisobola okwemelezaawo ensomesa mu lulimi Olusoga kuzwile nti Eiwanika ni lyonka elilina ebyetaagibwa okusimba omusingi gw’ebyendhegelesa mu lulimi Olusoga ebisobola okutuukana n’ebyetaago by’omukozesa aluubililwa mu kiseela kino. Waile ng’amakobo g’Eiwanika gaaliba gatuukana n’ebyetaago by’omukozesa ono, engeli ye gaategekebwa mu Iwanika teyanguyila mukozesa ono muyaaka kugeeyunila bukalamu. Okwinhonhola kw’amakobo g’Eiwanika kwasinga kukolebwa mu musomo amakobo gano mwegaasibuka. Kale kyaba nti amakobo agandi gazila bulungi businziilo mu Iwanika busobola kwetengelela kuyamba omukozesa aluubililwa. Ebyava mu kugezesa ensomesa y’ebyennnimi enzaalilanwa mu Uganda okwakolebwa ekitongole kya National Curriculum Development Centre byazuula nti omusomi ti ni yenka ayenda okutendekebwa aye n’omusomesa agya akusomesa yeena ayenda obuyambi. Engeli ebiwandiiko by’abaana abato bwe by’ekengelwa einho ate ng’omukozesa omuluubilile ow’Eiwanika yali muntu mukulu, eisila lili ku musomesa w’abasomi abo. Okutendeka omusomesa ono mu bimwetaagibwamu ng’asomesa Olusoga, akatabo akandi akalaga engeli y’okusomesaamu amakobo g’Eiwanika kaidha kuwandiikibwa okumulaga engeli y’ayinza okukozesa ebili mu nnhandhula ni mu nfaanana y’olulimi mu Iwanika okutegeka amasomo g’Olusoga ag’endhawulo. Waile nga kyali gwaine nti ebitabo ebita eisila ku nsomesa y’Olusoga mu pulaimale n’ebyalisinze kwetaagibwa, olupapula luno lusinziile ku mbeela eliwo buti ey’eibula ly’ensako n’abakugu abanoonheleza ku Lusoga, n’okusalawo okukozesa ekiwandiiko ekiliwo mu kiseela kino okugaziya emigaso gya kyo eli okutembeeta ensomesa y’olulimi Olusoga ng’esinziilwa ku Iwanika. Ebigambo ebikulu: EITEEKA LY’EBYENNIMI, ENDHEGELESA Y’ENNIMI ENZAALILANWA, OLUSOGA, UGANDA, ENTEGEKA Y’AMASOMO, OMUKOZESA WA P1–P3, OMUSOMESA WA PULAIMALE, ENTENDEKA Y’ABASOMESA BA PULAIMALE, WALIFU, GULAAMA, AMAKOBO GA KANALULIMI, EIWANIKA LY’OLULIMI OLULALA, EBIWANDIIKO BY’OMU BIKUGILO, ENFAANANA Y’OLULIMI, EBIFAANANI